Targeting Cbx3/HP1γ Induces LEF-1 and IL-21R to Promote Tumor-Infiltrating CD8 T-Cell Persistence - Le, Phuong T.; Ha, Ngoc; Tran, Ngan K.; Newman, Andrew G.; Esselen, Katharine M.; Dalrymple, John L.; Schmelz, Eva M.; Bhandoola, Avinash; Xue, Hai-Hui; Singh, Prim B.; Thai, To-Ha (Frontiers in Immunology, 2021)
Immune checkpoint blockade (ICB) can relieve CD8+ T-cell exhaustion in most mutated tumors, and TCF-1 plays an essential role. However, identifying mechanisms that can prevent functional senescence and potentiate CD8+ T-cell persistence for ICB non-responsive and resistant tumors remains elusive. We demonstrate that targeting Cbx3/HP1g in CD8+ T cells causes augmented transcription initiation and chromatin remodeling at Lef1 and Il21r leading to their increased transcriptional activity. LEF-1 and IL-21R are required for Cbx3/HP1g-deficient CD8+ effector T cells to persist and control ovarian cancer, melanoma and neuroblastoma in preclinical models. The enhanced persistence of Cbx3/HP1g-deficient CD8+ T cells facilitates remodeling of the tumor chemokine/receptor landscape ensuring their optimal invasion at the expense of CD4+ Tregs. Thus, CD8+ T cells heightened effector function consequent to Cbx3/HP1g deficiency may be distinct from functional reactivation by ICB, implicating Cbx3/HP1g as a viable cancer T-cell-based therapy target for ICB resistant, non-responsive solid tumors.